Review of the Blastobasinae of Costa Rica (Lepidoptera: Gelechioidea: Blastobasidae) - Adamski, David (Zootaxa, 2013)
The Blastobasinae (Lepidoptera: Gelechioidea: Blastobasidae) of Costa Ricaare reviewed. Five new genera, Barbaloba, Hallicis, Koleps, Pheos, and Pseudokoleps, and 101 new species are described. They include: Barbaloba jubae, B. meleagrisellae, Hallicis bisetosellus, H. calvicula, Koleps angulatus, Pheos aculeatus, Pseudokoleps akainae, Blastobasis abollae, B. achaea, B. aedes, B. babae, B. balucis, B. beo, B. caetrae, B. chanes, B. custodis, B. dapis, B. deae, B. deliciolarum, B. dicionis, B. echus, B. erae, B. fax, B. furtivus, B. iuanae, B. lex, B. litis, B. lygdi, B. manto, B. neniae, B. nivis, B. orithyia, B. paludis, B. phaedra, B. rotae, B. rotullae, B. tapetae, B. thyone, B. usurae, B. vesta, B. xiphiae, Hypatopa actes, H. acus, H. agnae, H. arxcis, H. bilobata, H. caedis, H. caepae, H. cladis, H. cotis, H. cotytto, H. crux, H. cyane, H. dicax, H. dolo, H. dux, H. edax, H. eos, H. erato, H. fio, H. gena, H. hecate, H. hera, H. hora, H. io, H. ira, H. leda, H. limae, H. lucina, H. joniella, H. juno, H. manus, H. mora, H. musa, H. nex, H. nox, H. phoebe, H. pica, H. plebis, H. rabio, H. rea, H. rego, H. rudis, H. sais, H. scobis, H. semela, H. solea, H. styga, H. texla, H. texo, H. umbra, H. verax, H. vitis, H. vox, Pigritia dido, P. faux, P. gruis, P. haha, P. sedis, P. stips, and P. ululae. Diagnoses, descriptions, and type data are provided for each species. Photographs of imagos, illustrations of wing venation for selected species, male and female genitalia, and distribution maps are furnished. Keys to all genera in Blastobasinae and keys to all species within each genus are provided to assist with identifications. In addition, scanning electron micrographs of the inner surface of the dilated first antennal flagellomere and associated sex scales for all Blastobasis are provided. Blastobasis coffeaella (Busck, 1925), B. graminea Adamski, 1999, Hypatopa tapadulcea Adamski, 1999, and Pigritia marjoriella Adamski, 1998 are redescribed.